El procedimiento civil como medio de control de la corrupción política: Formula octaviana y crimen repetundarum - González Romanillos, José Antonio (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2004)
This article treats on the active subjects of the formula Octaviana, private procedure that had as objective the protection of the provincial population of the spoliations made by the Roman citizens.